(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: This study aimed to describe the epidemiological and injury characteristics of hospitalized burn patients and evaluate inpatient treatment outcomes at Da Nang Hospital, Vietnam. Methods: A cross-sectional study was conducted at the Department of Burn Surgery and Plastic Surgery, Da Nang Hospital, from October 2025 to March 2026. A total of 75 hospitalized burn patients were enrolled using convenience sampling. Data on demographic characteristics, burn causes, burn agents, injury severity, treatment interventions, and clinical outcomes were collected from medical records and structured data forms. Descriptive statistics were analyzed using SPSS 27.0. Results: Patients aged 30–59 years accounted for the largest proportion (56.0%), and male patients predominated (66.7%). Domestic accidents were the leading cause of burns (69.3%), while dry heat (37.3%) and wet heat (36.0%) were the most common burn agents. Most patients were admitted within 8 hours after injury (58.7%). Burns involving less than 10% total body surface area accounted for 68.0% of cases, and deep burn areas below 10% were observed in 98.7% of patients. Upper extremities were the most commonly affected anatomical site (33.6%). Most patients had mild-to-moderate burns according to the American Burn Association classification. Conservative treatment was performed in 77.3% of patients, and debridement was the most frequent surgical procedure. The mean hospital stay was 12.04 ± 9.70 days. Most patients were discharged successfully (96.0%), and no in-hospital mortality was recorded. Conclusion: Burn injuries in this study were predominantly mild-to-moderate and mainly resulted from domestic accidents. Most patients had favorable treatment outcomes with relatively short hospital stays and low surgical intervention rates.